A Structural Model of Integrative Emotion Regulation, Perseverance, and Passion Among Student's Grit - Ahmad Rofi Suryahadikusumah; Ahman Ahman; Andre Julius; Hayinah Rahayu (Didaktika: Jurnal Kependidikan, 2026)
Madrasah students face challenges maintaining motivation and sustained interest amid the demands of dual education, so the ability to regulate emotions is crucial for maintaining consistent interest (passion) and perseverance in pursuing long-term goals. This study aims to test the structural model of the relationships among Integrative Emotion Regulation (IER), Passion (PAS), and Perseverance (PER) among madrasah students. The study administered a survey to 152 madrasah students in Serang and Cilegon City, used the Grit-S and Emotion Regulation Inventory instruments, and analyzed the data using Structural Equation Modeling (SEM). The results showed that the hypothesized model provided a good fit with the empirical data (χ² = 0.781, CFI = 1.000, RMSEA = 0.000), in which IER was a positive predictor of passion, and passion had a strong and significant direct effect on perseverance (β = 0.346). This study found that adaptive emotion regulation enables students to process emotional experiences constructively, laying the foundation for stable interests and persistent effort. This research significantly demonstrates that integrative emotion regulation is a psychological foundation that shapes students' passion and persistence in achieving long-term goals. The implications of this research indicate the need to develop regulation skills through guidance services to ensure students' consistency and ability to cope with high academic demands.